Bidirectional Associations Between Self-Reported Gaming Disorder and Adult Attention Deficit Hyperactivity Disorder: Evidence From a Sample of Young Swiss Men - Marmet, Simon; Studer, Joseph; Grazioli, Véronique S.; Gmel, Gerhard (Frontiers in Psychiatry, 2018)
Background Gaming disorder (GD) has been shown to co-occur with attention deficit hyperactivity disorder (ADHD), yet few studies to date have investigated their longitudinal associations. Method The sample included 5067 young Swiss men (mean age was 20 years at wave 1 and 25 years at wave 3). Measures were the Game Addiction Scale and the Adult ADHD Self-Report Scale (6-item screener). Longitudinal associations were tested using autoregressive cross-lagged models for binary measures of GD and ADHD, as well as continuous measures for GD score and ADHD subscales of inattention and hyperactivity. Results ADHD at age 20 increased the risk for GD at age 25 (probit=.066 [.023, .109]; p=.003). GD at age 20 also increased the risk for ADHD at wave 3 (probit=.058 [.013, .102]; p=.011). Only the ADHD inattention subscale showed a bidirectional longitudinal relationship with the GD score (standardized Beta from inattention at age 20 to GD score at age 25: .090 [.056, .124]; p < .001; from GD score at age 20 to inattention at age 25: .044 [.016, .071]; p = .002), whereas associations between the hyperactivity subscale and GD were not significant. Discussion GD had bidirectional longitudinal associations with ADHD, in that ADHD increased the risk for GD and GD increased the risk for ADHD, and they may reinforce each other. These associations may be linked more to the inattention ADHD component than to the hyperactivity ADHD component. Individuals with ADHD or GD should be screened for the other disorder, and preventive measures for GD should be evaluated in individuals with ADHD.